A comparison between barack obama's and trump's views towards mimorities : speech analysis - Labgaa, Widad; Ben redda ,Djamel (Faculty of Letters and Foreign Languages Department of English, 2018)
This thesis examined a comparison of two different American presidents Barack Obama and Donald Trump. This research examined their views to the category of minorities. Besides that, this research will include the status of the minorities in the American community and the difficulties. The main field of the study is “political discourse” that became one of the important domains that would analyze the thoughts of the politicians through their speeches; this means that language became a powerful tool in the society that one word can solve several problems. When it comes to politics is a domain that controls the daily life of the citizens. The modern lifestyle made the people interested in the political scene. The aim of this study is to encourage the students to get out of their comfort zone and try new domains of research. Also, politics could help the young generation to develop their critical thinking to see the different topics from different angles. On the other hand, English students mainly stuck in the domains of civilization and literature which would limit their vocabulary by practicing only the vocabularies that related to literature not other fields. This study highlights the issue of racism against the minorities in the political scene that the politicians are the one who encourage the hatred against this category. The hatred against the minorities would lead into a division in the American society ,even so it would lead to a second civil war